The forgotten mothers of extremely preterm babies: A qualitative study. Issue 11 (8th March 2019) - Fowler, Cathrine; Green, Janet; Elliott, Doug; Petty, Julia; Whiting, Lisa
Abstract: Aims and objectives: To explore the experiences of mothers of extremely premature babies during their Neonatal Intensive Care Unit stay and transition home. Background: Mothers of extremely preterm infants (28 weeks' gestation or less) experience a continuum of regular and repeated stressful and traumatic events, during the perinatal period, during the Neonatal Intensive Care Unit stay, and during transition home. Method: An interpretive description method guided this study. Ten mothers of extremely premature infants who had been at home for less than six months were recruited via a Facebook invitation to participate in semi‐structured telephone interviews exploring their experiences in the Neonatal Intensive Care Unit and the transition home. The data were examined using a six‐phase thematic analysis approach. The COREQ checklist has been used. Results: Two main themes emerged: (a) things got a bit dire; and (b) feeling a failure as a mother. Participants had a heightened risk of developing a mental disorder from exposure to multiple risk factors prior to and during birth, as well as during the postnatal period in the Neonatal Intensive Care Unit and their infant's transition to home. Mothers highlighted the minimal support for their mental health from healthcare professionals, despite their regular and repeated experience of traumatic events. Conclusion: The mothers were at high risk of developing post‐traumatic stress symptoms and/or other mental health issues. Of note, study participants relived the trauma of witnessing their infant in the Neonatal Intensive Care Unit, demonstrated hypervigilance behaviour and identified lack of relevant support needed when their infant was at home. Relevance to Clinical Practice: This study highlights the need for nurses to include a focus on the mothers' psychosocial needs. Supporting maternal mental health both improves maternal well‐being and enables mothers to be emotionally available and responsive to their extremely preterm infant.